A Preliminary Study on the Impact of Changing Shifting Cultivation Practices on Dry Season Forage for Asian Elephants in Sri Lanka. (December 2013) - Pastorini, Jennifer; Janaka, H. K.; Nishantha, H. G.; Prasad, Tharaka; Leimgruber, Peter; Fernando, Prithiviraj
Shifting cultivation, in which fields are traditionally cultivated for two or three consecutive years and left fallow for four to five years, is an ancient practice still prevalent in the dry zone of Sri Lanka. Traditionally, shifting agriculture is rain dependent and is limited to the wet season. However, traditional patterns are now changing due to population pressures. We assessed the use of shifting agriculture areas by Asian elephants ( Elephas maximus ) and the availability of fodder in active fields during the dry season, to evaluate the impact of changing cultivation practices on elephants. We radio-tracked a juvenile and an adult male, representative of the two social groupings of herds and adult males respectively, based on the sexually dimorphic social structure of elephants. Although the small sample size precluded definitive conclusions, the tracking data were consistent with extensive elephant use of shifting cultivation areas during the dry season. We conducted line transects and plots in fields cultivated continuously for 1-20 years, assessing the growth of grasses and four browse species selected as indicators of elephant food. Grass was plentiful in early dry season, representing an important but transient food source. Browse density and volume remained constant through the dry season. Browse density but not volume decreased with increasing number of consecutive years of cultivation. We conclude that shifting agriculture fields under active cultivation are a significant dry season food source for elephants. This benefit is likely to decrease with additional years of continued cultivation and/or longer cultivation seasons.